2011
DOI: 10.1016/j.nuclphysa.2011.05.071
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the LPM effect in a parton cascade model

Abstract: Parton Cascade Models (PCM [1][2][3][4]), which describe the full time-evolution of a system of quarks and gluons using pQCD interactions are ideally suited for the description of jet production, including the emission, evolution and energy-loss of the full parton shower in a hot and dense QCD medium. The Landau-Pomeranchuk-Migdal (LPM) effect [5,6], the quantum interference of parton wave functions due to repeated scatterings against the background medium, is likely the dominant in-medium effect affecting jet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…We have previously applied VNI/BMS [5] with a static medium to jets at LHC scales √ s = 2.76 ATeV, see Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously applied VNI/BMS [5] with a static medium to jets at LHC scales √ s = 2.76 ATeV, see Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…where E t, is the transverse energy of the leading jet and E t,s is that of the sub-leading jet, has been successfully reproduced by various authors with a variety of models [3][4][5][6]. Recent work by Renk [7] has indicated that these results may be relatively insensitive to the fine details of jet energy loss, suggesting that A j may be unsuitable for tomographic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…[25]). Recently we have experimented with implementing the LPM effect in a scheme that is assured to reproduce the BDMPS limit of parton energy-loss [26,27]. The energy loss suffered by charm quarks in an infinite medium (at a fixed temperature) was well described using this formalism [28].…”
Section: Model Descriptionmentioning
confidence: 99%
“…where E t, is the transverse energy of the leading jet and E t,s is that of the sub-leading jet. The asymmetry distribution measured in Pb+Pb collisions at the LHC has been successfully reproduced with a variety of models including the one considered here [4,5,6,7]. Recent work by Renk [8] indicates that these results may be relatively insensitive to the fine details of jet energy loss, suggesting that A j may be unsuitable for tomographic purposes.…”
Section: Introductionmentioning
confidence: 80%
“…In the VNI/BMS implementation of the PCM outgoing off-shell partons are brought back on-shell through a medium modified time-like branching. The partons created in this process are subject to a Monte-Carlo LPM effect [12,6]. The strong coupling constant for scatterings is held fixed at α s = 0.3 although we shall explore the effects of its variation below.…”
Section: The Parton Cascadementioning
confidence: 99%